2022
DOI: 10.3390/toxics10060315
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Alterations in the Livers of Chronic Hepatitis Patients Exposed to Agent Orange/Dioxin in Vietnam

Abstract: We investigated changes in some laboratory indices and the liver histology of chronic hepatitis patients who were exposed to dioxin. In 2014, we collected liver biopsy samples for histopathological examination from 33 chronic hepatitis patients living around the Da Nang Airbase, which is a dioxin-contaminated area due to the herbicide spraying in Vietnam. Dioxin exposure was measured by its levels in the blood. METAVIR classification was used to clarify the liver fibrosis stage. Laboratory tests included ten b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Exposure to dimethoate causes oxidative stress in lung by producing reactive oxygen species and the decreasing biological activities of some liver antioxidant enzymes such as catalase activity and glutathione -5-transferase [31]. Observations from this research strongly suggests hepatotoxic effects of dimethoate to the experimental animals and possible human.. Liver histopathology is the gold standard for diagnosis, assessing liver damage and identification of cause of the disease [32]. Congestion and round cell infiltration observed in the liver of rats treated with 600 or 800 mg/kg dimethoate and the focal necrosis at 800 mg/kg which were significantly higher than those of the control were signs of toxic damage to hepatocytes.…”
Section: Discussionmentioning
confidence: 79%
“…Exposure to dimethoate causes oxidative stress in lung by producing reactive oxygen species and the decreasing biological activities of some liver antioxidant enzymes such as catalase activity and glutathione -5-transferase [31]. Observations from this research strongly suggests hepatotoxic effects of dimethoate to the experimental animals and possible human.. Liver histopathology is the gold standard for diagnosis, assessing liver damage and identification of cause of the disease [32]. Congestion and round cell infiltration observed in the liver of rats treated with 600 or 800 mg/kg dimethoate and the focal necrosis at 800 mg/kg which were significantly higher than those of the control were signs of toxic damage to hepatocytes.…”
Section: Discussionmentioning
confidence: 79%
“…While animal models link TCDD to HCC, epidemiological studies in veterans have not been conclusive. These studies have been hindered by small or restricted sample sizes, short-term follow up, and a lack of consideration of other key clinical confounders for HCC, such as HCV and alcohol use, which are prevalent in veterans . Type 2 diabetes has also been linked to AO exposure and is recognized by the VHA as an AO-associated condition, which is also an independent risk factor for HCC .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have been hindered by small or restricted sample sizes, short-term follow up, and a lack of consideration of other key clinical confounders for HCC, such as HCV and alcohol use, which are prevalent in veterans. 18 , 19 , 20 , 21 , 22 Type 2 diabetes has also been linked to AO exposure and is recognized by the VHA as an AO-associated condition, which is also an independent risk factor for HCC. 23 Given the new government incentives to expand eligibility of veterans and the lack of strong data linking AO to HCC, large, statistically rigorous studies addressing the limitations of previous work are needed to better evaluate if AO as a clinically relevant risk for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Pham P.Q. et al [ 7 ] collected liver biopsy samples for histopathological examination from 33 chronic hepatitis patients living around the Da Nang Airbase. They found that increased TCDD levels in blood were associated with increased levels of liver function markers such as aspartate aminotransferase (AST), alanine aminotransferase (ALT), protein and total bilirubin, and high liver fibrosis stages classified using the METAVIR fibrosis staging system for histopathological examination.…”
mentioning
confidence: 99%